The Study of Government’s Role for Welfaring Rubber Farmer in The Globalization Vortex - Pahrudin HM (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2017)
Rubber is a type of plant that has been cultivated by the people of Indonesia for long a time. Until now, farmers have become the largest party to cultivate rubber in Indonesia (85.10%) and contribute greatly to the nation’s economy, but are still far from prosperous. Rubber products produced by farmers are priced cheap so that they incomes are very small and create income inequality. As an export commodity, rubber is highly dependent with overseas which determines the price. In this context, the government through the bureaucratic system serves to produce a series of innovative-solutive development program in order to keep the people from the negative impacts of globalization. This effort can be run by the government with adopting The New Public Service Paradigm as part of efforts to better public services for the people. It is implementation in the form of domestic rubber needs priorities, bringing the industry to the center of rubber, training of rubber farmers, and improvement of transportation infrastructures.